2016
DOI: 10.1007/s40272-016-0193-1
|View full text |Cite
|
Sign up to set email alerts
|

Tablet Splitting of Antiepileptic Drugs in Pediatric Epilepsy: Potential Effect on Plasma Drug Concentrations

Abstract: Splitting adult-dosage formulations of AEDs results in patients not receiving the optimal dose. Plasma drug concentrations are also not optimal. Pediatric dosage formulations should be preferred to splitting adult-dosage formulations in pediatric epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…A divisão dos comprimidos foi um dos erros frequentemente identificados no estudo, visto que é rotina usual entre pediatras esta orientação como forma de adequação da dose, dada a indisponibilidade de formas farmacêuticas líquidas. Sabe-se que a divisão do comprimido de anticonvulsivantes leva a uma falta de uniformidade de peso ou de conteúdo do princípio ativo ao fracionar o comprimido 21 . Uma revisão recente realizada por Richey et al em 2017 demonstrou que há uma escassez de evidências para apoiar a manipulação de drogas em crianças, sendo necessário avaliar o impacto da manipulação na precisão da dosagem e a necessidade da própria indústria farmacêutica incluir nos programas de desenvolvimento de medicamentos o efeito da manipulação dos comprimidos 22 .…”
Section: Discussionunclassified
“…A divisão dos comprimidos foi um dos erros frequentemente identificados no estudo, visto que é rotina usual entre pediatras esta orientação como forma de adequação da dose, dada a indisponibilidade de formas farmacêuticas líquidas. Sabe-se que a divisão do comprimido de anticonvulsivantes leva a uma falta de uniformidade de peso ou de conteúdo do princípio ativo ao fracionar o comprimido 21 . Uma revisão recente realizada por Richey et al em 2017 demonstrou que há uma escassez de evidências para apoiar a manipulação de drogas em crianças, sendo necessário avaliar o impacto da manipulação na precisão da dosagem e a necessidade da própria indústria farmacêutica incluir nos programas de desenvolvimento de medicamentos o efeito da manipulação dos comprimidos 22 .…”
Section: Discussionunclassified
“…[14] Although there are no comparable studies of AEDs, studies with other groups of drugs found no difference in the lipid profiles of patients treated with split or whole statin tablets. [151617] The findings of these studies are contradictory to our findings; this may be because the endpoint was change in lipid levels rather than plasma drug concentration as well as the fact that the formulation may be suited for splitting.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting study looked at whether splitting of adult tablets for pediatric use provides adequate content uniformity of four antiepileptic drugs (Nidanapu et al, 2016). Of the 1098 split tablet parts analyzed, nearly half were above the specified limit, leading the authors to recommend that pediatric dosage formulations and not adult split-tablets should be used in children.…”
Section: Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%